Значення "Положення про нотаріальну частину" 1866 року для розвитку нотаріату в Україні - Ільїна, Юлія Павлівна (My University, 2010)
В данной статье анализируется "Положение о нотариальной части" 1866 года как один из основных фундаментов формирования нотариата в современной Украине.

This article analyzes the «Regulations on the part of the notary» in 1866 as one of the main foundations of notaries in the formation of modern Ukraine.
Keywords: положення про нотаріальну частину; нотаріат; розвиток нотаріату; формування нотаріату; положение о нотариальной части; нотариат; развитие нотариата; формирование нотариата; Regulations on the part of the notary; notary; development of notary; formation of Notaries